Binongko Multiplication: An Ethnomathematics Method to Adress Mathematical Challenges Among the Butonese Ethnic Group in Masohi City - Aspin, La; Lessy, Djaffar; Sopamena, Patma (Faculty of Teacher Training and Education, 2025)
Ethnomathematics is defined as the specific methods used by a particular cultural group or society in mathematical activities. This study aims to explain the elements of ethnomathematics found in the term kali-kali binongko and how it can be applied in mathematics learning. The method used in this article is an ethnographic approach, with a qualitative research design. Data were collected through semi-structured interviews, observation, and documentation. The data analysis process in this study consisted of three stages: data reduction, data presentation, and drawing conclusions. The results of this study reveal the presence of ethnomathematics in the application of kali-kali binongko among the Buton tribe in Masohi City. The ethnomathematical aspects of kali-kali binongko practiced by the Buton tribe in Masohi can be explained through three main findings: (1) The history and culture of the Buton tribe, (2) Ethnomathematical elements found in kali-kali binongko, including: a. Number systems, b. Determining marriage dates, c. Mathematical knowledge in agricultural practices, d. Mathematical knowledge in fishing activities, and e. The application of kali-kali binongko in trading activities, (3) The discovery of a mathematical concept referred to as “hidden mathematics” or “frozen mathematics” among the Buton tribe, which includes naming counting activities based on the number of days in a new month, following the traditional practice of counting the moon’s phases in the sky.